Does Linking Teacher Pay to Student Performance Improve Results? - World Bank (World Bank, Washington, DC, 2012)
Educators and education policy makers are concerned with creating the best possible learning environment for students. How to do this, especially in primary school, where reading, writing and mathematical skills are first acquired, is the subject of policy debates in many parts of the world. Should teachers be paid more? Can students be rewarded for good test results? Do schools need more supplies and better infrastructure? Should parents have access to better information about the quality of schools and parental rights and responsibilities? There are no clear answers yet. The World Bank supported a study of government-run primary schools in the state of Andhra Pradesh in India. The project, incorporating 500 schools, concluded that giving teachers cash bonuses based on the improvement in student performance was more effective at raising test results than giving schools cash grants for supplies or additional teachers. This project, which looks at only one school system in one country, will not end the debate over how to boost student performance. But it does offer a piece of the puzzle to help steer policy makers and educators as they move forward with new educational programs and projects.